The making of Israel: cultural diversity in the Southern Levant and the formation of ethnic identity in Deuteronomy - Crouch, C.L. (Brill, 2014)
In The Making of Israel C.L. Crouch presents the southern Levant during the seventh century BCE as a major period for the formation of Israelite ethnic identity, challenging scholarship which dates biblical texts with identity concerns to the exilic and post-exilic periods as well as scholarship which limits pre-exilic identity concerns to Josianic nationalism. The argument analyses the archaeological material from the southern Levant during Iron Age II, then draws on anthropological research to argue for an ethnic response to the economic, political and cultural change of this period. The volume concludes with an investigation into identity issues in Deuteronomy, highlighting centralisation and exclusive Yahwism as part of the deuteronomic formulation of Israelite ethnic identity.